EFL TEACHERS’ AND STUDENTS’ PERCEPTION ABOUT E-LEARNING IN THE ENGLISH SUBJECT: A STUDY AT ISLAMIC STATE UNIVERSITY OF ALAUDDIN MAKASSAR - Ima, Nur; Anggung, Sinta Dewi; Alimuddin, Andi Haeriati (Inspiratif Pendidikan, 2023)
This study highlighted teachers’ and students’ perception in order to investigate teachers’ and students’ perception about e-learning when English subject is concerned. The population of this study was the seventh semester of the English Education department of UIN Alauddin Makassar who have experienced in implementing e-learning in teaching and learning activities. Sixteen students and four lecturers were involved as a sample of the study. This study employed quantitative method were the data collected by using Questionnaire that is consisting 24 items based on likert scale. The data showed that there were above 62,2% of respondents gave positive responses, 28,5% stated neutral, and 9,79% disagree.